Experimental performance and emissions of additively manufactured high-temperature combustion chambers for micro-gas turbines. (April 2023) - Adamou, Adamos; Costall, Aaron; Turner, James W.G.; Jones, Andy; Copeland, Colin
To date, 59 countries, representing 54% of global greenhouse gas emissions have made pledges for net-zero emissions targets within this century. This will require cleaner and more efficient sources of energy which is driving research into small-scale engines and auxiliary power units for hybrid vehicles and stationary power generation. A suitable candidate for such applications is the micro gas turbine due to its high-power density, reliability and low emissions. Further development of such engines is required though due to their increasing parasitic energy losses relative to net power output as size decreases. Additive manufacturing offers the design freedom to not only increase efficiencies but to also reduce emissions when applied to the various components of micro gas turbines. This article reports the effects of several additive manufacturing (AM) enabled design features for micro gas turbine combustion chambers via experimental testing of full-scale parts. The main objective of the additively manufactured features is the reduction of exhaust emissions by improving the air-fuel mixture distribution and consequently ignition and combustion. Using additive manufacturing a novel conical radial swirl-stabilized tubular combustor with internal vane fuel injection was created as a baseline for the laboratory testing. Several other features, including augmented backside liner cooling surfaces, in-vane lattice structures for fuel mixing and upstream liner fuel injection rings were also generated to further the investigations into additively manufactured features and their effects on fuel mixing. Using multiple combinations of all these features, 10 geometries were generated and tested at a variety of operating conditions. Three inlet temperatures were tested (500°C, 600°C and 700°C) with varying fuel flow rates to investigate their operating limits at a constant inlet pressure of 4 bar absolute. Test results for the full range of equivalence ratios and operating conditions showed that the upstream liner fuel injection designs generated NOx, CO and THC emissions on par with the baseline but showed a reduction in the maximum and minimum operating ranges. This design, however, demonstrated the distinct advantage of being able to ignite at full air mass flow; this is not possible with the baseline designs and is also an added benefit to its main use which is the reduction of liner temperature. Overall, the test results underscore that designing combustion chambers for additive manufacturing can provide a myriad of benefits not only for micro gas turbines but also for other applications requiring high efficiency combustion chambers.